Indium antimonide uncooled photodetector with dual band photoresponse in the infrared and millimeter wave range - Tong, Jinchao (2020)
All-InSb film-based and spiral antenna-assisted Au-InSb-Au metal-semiconductor-metal detector is reported with dual-band photoresponse in the infrared (IR) and millimeter wave range. At IR, the detector exhibits a long wavelength 100% cut-off at 7.3 µm. Under an applied bias of 5 mA, the uncooled blackbody responsivity and specific detectivity are 3.5 A/W and 1×108 Jones, respectively. The f-3dB value measured at 2.94 µm is 75 KHz, corresponding to a detector rise speed of 4.7 µs. At millimeter wave range, the detector shows a narrowband response determined by the coupling of the antenna. A voltage responsivity of 25 V/W is achieved at 167 GHz (1.796 mm) under an applied bias of 25 mA, and the corresponding noise equivalent power (NEP) is 1.0×10-10 WHz-1/2, which can be improved to 1.8×10-12 WHz-1/2 if normalized to the real active semiconductor area. A f-3dB value of 17.5 KHz, corresponding to a detector rise speed of 20 µs is achieved in this range. A proof of principle for IR-modulated photoresponse for millimeter wave is achieved with a maximum modulation depth of 47.5%. This All-InSb film-based detector and the modulation are promising for future novel optoelectronic devices in IR and millimeter waves.